Existence and stability of triangular points in the relativistic R3BP when the bigger primary is a triaxial rigid body and a source of radiation - Singh, Jagadish; Nakone, Bello (International Journal of Advanced Astronomy, 2016)
We study the effect of triaxiality and radiation of the bigger primary on the positions and stability of the triangular points in the relativistic R3BP. It is found that the locations of the triangular points are affected by the relativistic terms apart the radiation force and the triaxiality of the bigger primary. It is also seen that for these points, the range of stability region increases or decreases according as without which depends upon the relativistic terms, the radiation and triaxiality coefficient is greater than or less than zero. A practical application of this model could be the study of the motion of a dust grain particle near the Sun-Earth system. A practical application of this model could be the study of the motion of a dust grain particle near the Sun-Earth system.